Hukum Ekonomi Syariah dan Solusi Pengangguran Melalui Pendekatan Praktis dan Teoritis - Gini Gaussian; Yusup Bagja (STAI Al Musaddadiyah Garut, 2026)
Unemployment is one of the most pressing issues in the Indonesian economy, especially in rural areas such as Mekarsari Village, Cilawu District, Garut. Unemployment is a significant challenge that hinders economic growth and community welfare in the Mekarsari Village area. So that the formulation of the problem arises: What are the factors causing the high unemployment rate in Mekarsari Village, Cilawu District, Garut, How can the application of Sharia Economic Law help reduce unemployment in Mekarsari Village, and What are the programs or initiatives that have been implemented in Mekarsari Village to overcome unemployment through a sharia approach. The objectives to be achieved from this study are to determine the factors causing the high unemployment rate in Mekarsari Village, Cilawu District, Garut, To determine the application of Sharia Economic Law can help reduce unemployment in Mekarsari Village and To determine the programs or initiatives that have been implemented in Mekarsari Village to overcome unemployment through a sharia approach. The research method used by the researcher is qualitative with data collection through in-depth interviews, observation, and document analysis. The results of the study indicate that the implementation of Sharia Economic Law, through community empowerment programs and sharia-based business development, significantly reduces the unemployment rate, strengthens MSMEs, and improves the welfare of the Mekarsari Village community. This study is expected to contribute to the development of more effective sharia economic policies at the local level. the Mekarsari Village community. It is hoped that this research can contribute to the development of more effective sharia economic policies at the local level.Keywords: Law; Sharia Economics; Unemployment, Community Empowerment